Analysis of Inflation Targets in Indonesia During The New Normal Era: New Consensus Approach to an Open Economy - Arno, Abdul Kadir; Ilham, Ilham; Sabani, Akbar; Purnama, Iksan (Jurnal Iqtisaduna, 2020)
This article aims to discuss a growth model in terms of demand constrained by economic policy with inflation targeting in a super multiplier sraff model by analyzing how economic policy can affect productive capacity growth. This article also analyzes the open economy if inflation is a phenomenon resulting from the policy of the monetary authority that can manage the nominal exchange rate through changes in interest rates. Since the distribution of functional income will depend on the evolution of nominal wages, exchange rates and interest rates, we will show that the inflation targeting system, apart from being neutral in terms of long-term growth, can also produce different results in terms of the distribution of functional income